The Effects of Inflation and Joblessness on Regional GDP in Seven West Javan Cities from 2014 to 2021 - Putri, Vera Ridia Insani; Marliana, Nissa Ayu; Husaini, Fauzan; Nurshadiqah, Samira (Syari'ah Economics, 2023)
This study examines the impact of inflation and unemployment on gross regional domestic product in seven cities in West Java Province during the period 2014-2021. Using quantitative methods and associative research approaches, secondary data were obtained from the West Java Central Bureau of Statistics. The variables examined include inflation, unemployment, and economic growth measured by GRDP at constant prices. The analysis was conducted using panel data regression using a common effect model. The results show that inflation has a negative effect on GRDP, while unemployment has a positive effect on GRDP in seven cities.